Contribution of the energy integration to the clean production in a furfural’s byproducts plant of Chemical Bioactive Center - Rodríguez Machín, Lizet; Espinosa Pedraja, Rubén; Cruz Fonticiella, Oscar Miguel (Centro Azúcar Journal, 2008)
In this work there are applied energy integration principles to a particular technology, per production lots (batch), employed in the Center of Chemical Bioactive (CBQ) for producing active pharmaceutical ingredients from furfural. This strategy contributes to a clean production in the production plant because it minimizes the emission of gaseous wastes. In this context, it is determined he quantity of combustion gases not generated by concept of the net reduction of fuel consumption, which is the result of a better integration process. The results achieved are promising because the conditions of the production workshops as well as surrounding areas will notably improve.